Perencanaan dan Perancangan Bojonegoro Creative Hub dengan Pendekatan Konsep Arsitektur Modern - Miarsono, Harry; Aguswin, Ahmad; Supriyanto, Supriyanto; Firdaus, Lukman (Attractive : Innovative Education Journal, 2022)
This research discusses the planning and design of Bojonegoro Creative Hub as the main supporter of creative economic development in Bojonegoro Regency, East Java. Focusing on the Modern Architecture concept approach, the research integrates modern elements with local symbols, particularly the cultural value of the Bengawan Solo River. The research method involves literature study, field survey, and design analysis to illustrate the integration of the concept. The results of this research provide practical guidance for the development of similar projects, highlighting the importance of integrating modern innovations with local cultural roots. It is expected that the implementation of Modern Architecture concepts with local values, such as the Bengawan Solo River, can encourage creative economic growth and strengthen local identity. The findings support efforts to realize Bojonegoro's economic and cultural potential in a sustainable manner. Keywords: Bojonegoro Creative Hub, Modern Architecture, Local Cultural Values